Artificial Intelligence And Content Creation Workshops Determine Youth Technology Literacy: Lokakarya Kecerdasan Buatan Dan Pembuatan Konten Menentukan Literasi Teknologi Pemuda - Sofi Intan Febrianti; Isnaini Rodiyah; Muhamad Hendrik; Sabeth Mochammad Rizki; Irsalina Khoirilia (International Consortium of Education and Culture Research Studies, 2025)
General Background The rapid evolution of information and communication systems necessitates strict technical mastery within modern educational frameworks to prepare the younger generation for global competition. Specific Background Indonesian educational institutions consistently face significant digital divides and limited access to integrated multimedia application instruction. Knowledge Gap Despite theoretical demands for software literacy, practical opportunities for students to acquire advanced multimedia capabilities and practical application experience remain severely restricted in the field. Aims This study evaluates a targeted instruction program focusing on design, video editing, artificial intelligence, and online media management at SMA Negeri 1 Porong. Results Quantitative descriptive evaluations demonstrate that structured sessions successfully establish student confidence and technical proficiency across multiple platforms, including Canva, CapCut, and various algorithmic generators. While baseline software familiarity existed among participants, targeted instruction successfully formed advanced technical executions and strategic social media planning. Novelty This research distinctly maps the transition of secondary students from passive consumers to confident digital creators through integrated, personalized application modules. Implications Educational institutions must implement continuous, personalized instruction featuring intensive practical exercises to ensure consistent software proficiency and advanced skill mastery among the younger generation. Highlights: Structured software instruction establishes strong student confidence across various editing platforms. Participants successfully mastered advanced design applications and online media management strategies. Continuous practical exercises remain necessary to ensure consistent software proficiency levels. Keywords: Digital Skills, Editing Applications, Social Media Optimization, Artificial Intelligence, Student Proficiency